Electrical versus pharmacological cardioversion for emergency department patients with acute atrial fibrillation (RAFF2): a partial factorial randomised trial. Issue 10221 (1st February 2020) - Stiell, Ian G; Sivilotti, Marco L A; Taljaard, Monica; Birnie, David; Vadeboncoeur, Alain; Hohl, Corinne M; McRae, Andrew D; Rowe, Brian H; Brison, Robert J; Thiruganasambandamoorthy, Venkatesh; Macle, Laurent; Borgundvaag, Bjug; et al.
Summary: Background: Acute atrial fibrillation is the most common arrythmia treated in the emergency department. Our primary aim was to compare conversion to sinus rhythm between pharmacological cardioversion followed by electrical cardioversion (drug–shock), and electrical cardioversion alone (shock-only). Our secondary aim was to compare the effectiveness of two pad positions for electrical cardioversion. Methods: We did a partial factorial trial of two protocols for patients with acute atrial fibrillation at 11 academic hospital emergency departments in Canada. We enrolled adult patients with acute atrial fibrillation. Protocol 1 was a randomised, blinded, placebo-controlled comparison of attempted pharmacological cardioversion with intravenous procainamide (15 mg/kg over 30 min) followed by electrical cardioversion if necessary (up to three shocks, each of ≥200 J), and placebo infusion followed by electrical cardioversion. For patients having electrical cardioversion, we used Protocol 2, a randomised, open-label, nested comparison of anteroposterior versus anterolateral pad positions. Patients were randomly assigned (1:1, stratified by study site) for Protocol 1 by on-site research personnel using an online electronic data capture system. Randomisation for Protocol 2 occurred 30 min after drug infusion for patients who had not converted and was stratified by site and Protocol 1 allocation. Patients and all research and emergency department staff were masked to treatment allocation for Protocol 1. The primary outcome was conversion to normal sinus rhythm for at least 30 min at any time after randomisation and up to a point immediately after three shocks. Protocol 1 was analysed by intention to treat and Protocol 2 excluded patients who did not receive electrical cardioversion. This study is registered at ClinicalTrials.gov, number NCT01891058 . Findings: Between July 18, 2013, and Oct 17, 2018, we enrolled 396 patients, and none were lost to follow-up. In the drug–shock group (n=204), conversion to sinus rhythm occurred in 196 (96%) patients and in the shock-only group (n=192), conversion occurred in 176 (92%) patients (absolute difference 4%; 95% CI 0–9; p=0·07). The proportion of patients discharged home was 97% (n=198) versus 95% (n=183; p=0·60). 106 (52%) patients in the drug–shock group converted after drug infusion only. No patients had serious adverse events in follow-up. The different pad positions in Protocol 2 (n=244), had similar conversions to sinus rhythm (119 [94%] of 127 in anterolateral group vs 108 [92%] of 117 in anteroposterior group; p=0·68). Interpretation: Both the drug–shock and shock-only strategies were highly effective, rapid, and safe in restoring sinus rhythm for patients in the emergency department with acute atrial fibrillation, avoiding the need for return to hospital. The drug infusion worked for about half of patients and avoided the resource intensive procedural sedation required for electrical cardioversion. We also found no significant difference between the anterolateral and anteroposterior pad positions for electrical cardioversion. Immediate rhythm control for patients in the emergency department with acute atrial fibrillation leads to excellent outcomes. Funding: Heart and Stroke Foundation of Canada and the Canadian Institutes of Health Research.